Study of biological activity of Eruca sativa as antimicrobial agent - H. Al_Ameri, Kudair; K.Baker, Rajaa; A.Al_khusa, Duaa.; M.Al_tememi, Ahmed (Al-Qadisiyah Journal of Pure Science, 2018)
The antimicrobial activity of Eruca sativa extract was tested against various Gram-positive and Gram-negative bacteria as well as yeast. Ethanol extract showed better activity against the tested bacteria compared to the yeast. Minimum inhibitory concentration of the extract was 100 gm/ml. Active compounds alkaloid; glycoside, flavonoids and saponins were revealed by the photo chemical analysis.